Evaluation of Psychophysiological and Hormonal Changes in Acute and Chronic Forms of Central Serous Chorioretinopathy - A. A. Shchuko; S. I. Kolesnikov; T. N. Iurevа; A. N. Zlobina (Acta Biomedica Scientifica)
Aim: to evaluate changes in the parameters of the visual system, psycho-physiological reactions (psychoemotional changes), and hormonal changes in patients with central serous chorioretinopathy and on this basis to develop a conceptual scheme for the activation of pathogenetic mechanisms of the formation of acute and chronic forms of the disease. Material and methods. 40 people with central serous chorioretinopathy and 26 control subjects were examined with the assessment of psychophysiological (psychoemotional) and hormonal changes.Results. The most informative criteria have been identified which determine various forms of the clinical course of central serous chorioretinopathy: the area of damage to the retinal pigment epithelium, psycho-emotional changes (the difficulties of role-playing, dependence on other people in domestic and professional environment, a high degree of reactive and personal anxiety, paranoia and level of distress), violation of the psycho-physiological characteristics of the state of the visual system, changes in hormonal regulation (cortisol, thyroid hormones, dehydroepiandrosterone, melatonin, 17-OH-progesterone, testosterone).Conclusion. The complex of psychophysiological changes that form the basis for the pathogenesis of central serous chorioretinopathy, according to the feedback mechanism, enhances the initial moments of the disease, exacerbates the severity of clinical manifestations and leads to chronicity of the pathological process, causing, thus, the complexity of diagnosis and treatment of central serous chorioretinopathy.